STUDI TENGGANG WAKTU PENGGUNAAN DAGING IKAN GABUS PADA PEMBUATAN PEMPEK LENJER - Fajri, M.; Dasir, Dasir (Universitas Muhammadiyah Palembang, 2017)
This study aims to know the effect of storage time limit catfish meat to protein content pempek lenjer gabus. Knowing fish meat storage time limit the influence of catfish to the organoleptic pempek lenjer Gabus fish. This study was conducted in laboratory Faculty of Agriculture, University of Muhammadiyah Palembang in May 2016 to the month of February 2017. This study uses a randomized block design (RAK) are arranged in a nonfactorial factors meat storage time limit of five catfish repeated treatments and four replications. The parameters observed in this study, for chemical analysis includes protein content pempek catfish. As for organoleptic observed variables including color, aroma, taste and level of resilience as well as physical test includes volume development. The grace period catfish meat storage very significant effect on the protein content pempek lenjer catfish. Treatment P0 (0 days of storage in the refrigerator / control) generates the highest protein content with an average value of 10.61%. The highest preference level value to the colors found in P4 treatment with an average value of 3.92 (criterion rather liked). A level of the highest value to the aroma, taste and level of resilience found in treatment P0 with average values of 4.12, 4.12 (criteria like) and 0.56 (a chewy criteria). The grace period catfish meat storage very significant effect on the volume of development pempek lenjer catfish. P4 treatment (8 days of storage in the refrigerator) produce the highest volume of development with an average value of 72.51%. Treatment P0 (0 days of storage in the refrigerator / control) produces good treatment and treatment P4 (8 days of storage in the refrigerator) produce treatment is still suitable for consumption. To obtain pempek lenjer catfish was good and rather preferred by the panelists are advised to use the treatment P3 (6 days of storage in the refrigerator).